Redobro de possessivos: o desaparecimento em português e o surgimento em francês - Calindro, Ana Regina (2024)
Our goal is to analyze the disappearance of 3rd person possessive doubling in Portuguese ( seu N dele), and its emergence in French (son N à lui). The main difference is that in French, possessives are deficient clitics, while in Portuguese, they are strong and weak pronouns. Possessive doubling disappeared in Portuguese due to the change in the pronoun paradigm, with the entry of new elements, as você. Thus, deficient elements were replaced by strong pronouns and no longer appear in doubling structures. In French, doubling occurs because a deficient element may co-occur with a strong element that allows them to give a full interpretation to their referent, in the case of possessives, it may either be the possessor or the possessed element. However, it is not always necessary for referents to have this full interpretation, i.e., possessive doubling is not mandatory, as it is used pragmatically when it is necessary to solve some referential ambiguity or emphasize possession relations, as in French.